PROMOSI KESEHATAN DAN DETEKSI DINI KANKER SERVIKS DENGAN INSPEKSI VISUAL ASAM ASETAT (IVA) - Lenna Maydianasari; Nonik Ayu Wantini; Jacoba Nugrahaningtyas Wahjuning Utami; Melani Maranressy; Fika Handayani (Lembaga Penelitian Dan Pengabdian Masyarakat Politeknik Kesehatan Muhammadiyah Makassar, 2022)
The coverage of the IVA examination at the Kalasan Health Center in 2021 was 77 people from the target of 13,517 (0.56%). The fear of cancer is also a cause for women to be reluctant to do early detection which results in distancing themselves from various information about cancer. Good knowledge about cervical cancer can reduce fear and shame so that women's awareness of early detection of cervical cancer appears. . Therefore, health promotion efforts with counseling on early detection of cervical cancer are important to provide a correct understanding to women. Early detection of cervical cancer using the Acetic Acid Visual Inspection (IVA) method. This method was chosen because the technique is easy/simple, low cost/cheap and the sensitivity level is high, fast and accurate enough to find abnormalities at the stage of cell abnormalities (dysplasia) or before precancer. Health promotion activities and early detection of cervical cancer with IVA will be held in August and September 2022. The results showed an increase in knowledge after counseling and IVA examination, 4 positive results were obtained